The Influence The Influence Of Leadership Style And Work Environment On Employee Job Satisfaction At PT Meroke Remains Jaya - Rezha Mahendra; Anita Asnawi; Damajanti Sri Lestari (Cita Konsultindo Research Center, 2026)
This study aims to analyze the contributions of Leadership Style (X1) and Work Environment (X2) to Employee Job Satisfaction (Y) at PT Meroke Tetap Jaya, both individually and simultaneously. Employing a quantitative causal-associative approach, the sample size was determined using Cochran's formula, resulting in 96 employee respondents selected via proportionate stratified random sampling. Primary data were collected using a Likert-scale questionnaire. Multiple linear regression analysis yielded the model Y = 0.236 + 0.311X1 + 0.317X2. Partial tests (t-tests) showed a calculated t-value of 6.800 (p=0.000 < 0.05) for Leadership Style and 3.262 (p=0.002 < 0.05) for Work Environment, indicating that both independent variables have a positive and significant effect on job satisfaction. The simultaneous test (F-test) resulted in a calculated F-value of 83.580 (p=0.000 < 0.05), confirming that leadership and work environment collectively have a significant impact on employee job satisfaction. An Adjusted R-Square value of 0.635 indicates that 63.5% of the variation in job satisfaction can be explained by these two independent variables, while the remaining 36.5% is influenced by variables outside the scope of this study.